Pemodelan dan prediksi jumlah penumpang pelabuhan bakauheni selama periode tsunami Selat Sunda menggunakan autoregressive integrated moving average - Dani Al Mahkya; Dian Anggraini; Andi Fitriawati; Radot MH Siahaan (Journal of Science and Applicative Technology, 2020)
Bakauheni Port is a ferry port located in Bakauheni District, South Lampung. This port is one of the major ports located on Sumatera island connecting Sumatera and Java and is located in the Sunda Strait. The tsunami that occurred in the Sunda Strait on December 22, 2018 indirectly affected the sea crossing node, especially the Bakauheni-Merak route. This can lead to changes in time series data patterns. The phenomenon is expected to be captured through a mathematical modeling that can be used as a decision making in the future. The purpose of this study was to model and predict the number of Bakauheni port passengers during the Sunda Strait Tsunami period using the Autoregressive Integrated Moving Average (ARIMA). The ARIMA approach uses past information as a basis for modeling. Based on visual information on the number of Bakauheni Port passengers, there was an increase in December in general. Other information is that there are seasonal patterns that occur with a span of 7 days. This was indicated by the pattern of repeated increases in the number of passengers every Sunday. After the tsunami, the number of passengers decreased for 2 days. In the 3 days after the Tsunami or during the Christmas holiday on December 25, 2018, the number of passengers has increased again. Based on the analysis and discussion that has been done, the best time series model obtained is ARIMA([5],1,2)(2,1,0)7 with a Mean Absolute Percentage Error (MAPE) of 9.55%.